Gastric carcinoma and renal cell carcinoma as an atypical presentation of multiple primary malignancies: a case report and review of the literature - Martín-Pérez, J. A. (J Med Case Rep, 2020)
BACKGROUND: Gastric carcinoma (GC) with second primary malignancy (SPM) is the most frequent combination within the multiple primary malignancies (MPM) group. The presentation of a GC associated with a synchronized SPM in the kidney is extremely rare and unusual. This study presents a rare case of synchronous tumors, describes the main associated risk factors, and emphasizes the need to rule out SPM. MAIN BODY: We present the case of a 63-year-old Hispanic woman with a history of smoking, weight loss, and gastrointestinal (GI) bleeding. GC was diagnosed by endoscopy, and during her workup for metastatic disease, a synchronous SPM was noted in the left kidney. The patient underwent resection of both tumors with a satisfactory postoperative course. A systematic review of the literature was performed using the Medline/PubMed, Science Direct, Scopus, and Google Scholar databases. A search of the literature yielded 13 relevant articles, in which the following main risk factors were reported: the treatment utilized, the grade and clinical stage, histopathological report, and in some cases survival. It is concluded that advanced age (> 60 years) and smoking are the main associated risk factors. CONCLUSION: Gastric carcinoma is the second most frequent neoplasm of the GI tract and the main neoplasm that presents a SPM. MPM screening is recommended in patients with gastric cancer. The clinical discovery of MPM of renal origin is rare and hence the importance of the current report.